Hadith about Educational Curriculum - Darliana Sormin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Education is a conscious effort made by humans to humanize humans. This is done in order to empower all potential so that human beings are in accordance with their nature. Human nature, nowadays, is increasingly marginalized by worldly forms. At its culmination point, humans no longer understood their nature as Caliph fi al-ardh which coincided with the purpose of the creation of jinn and humans in order to serve the Creator. In line with efforts to humanize humans who have humanized education harmonized with human needs in their time. It is this change in human needs that leads people to keep up to date, which is in line with the times. Because, the age that continues to develop in accordance with rapid civilization can moralize specific needs. Specifications of human needs for material. The higher human intelligence, the more curiosity and the more problems and challenges in life. To answer these problems and challenges, various branches of science were born. Even so, essentially, Islamic Education is the foremost part that must be developed to the root of life's problems. Because, humans who are naturally created by God must remain in the order of life guided by Islam.